(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
The study aimed to demonstrate the impact of the customer relationship management (CRM) program dimensions on customer service at Saudi Telecom Company, and to demonstrate the difficulties and challenges facing the implementation of the customer relationship management (CRM) program in dealing with customer service. the descriptive analytical approach was used for the study, and a questionnaire was used as a study tool. a simple random sample was selected from the study community, which includes administrative employees at Saudi Telecom Company in Jeddah, numbering (177) administrative employees. one of the most prominent results was that individuals from senior management gave a higher evaluation of the role of the (CRM) program in enhancing cooperation with the company’s sectors, compared to executive management. This indicates that the strategic awareness of the program’s role may be more evident among the upper echelons of the job structure. the results also showed clear differences according to academic qualifications and years of experience, as individuals with higher qualifications and long years of experience tend to evaluate the program’s dimensions with a higher degree. this reflects a deep understanding of the various dimensions of the (CRM) program, such as allocating services to major customers and developing organizational structures that support customers. among the main challenges revealed by the study are weak direct communication and the reliance on automated responses to customer inquiries, which reduces the quality of communication and weakens customer satisfaction with the program. the study recommended focusing on major customers and providing them with tailored services. major customers are considered the most important pillars that enable a company to outperform its competitors. Therefore, the company must constantly strive to retain them by meeting their needs and desires.